2000
DOI: 10.1111/j.1744-6570.2000.tb00206.x
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Technology Adoption Decisions: Implications for a Changing Work Force

Abstract: This research investigated age differences in individual adoption and sustained usage of technology in the workplace using the theory of planned behavior. User reactions and technology usage behavior were studied over a 5-month period among 118 workers being introduced to a new software system. At 2 points of measurement, compared to older workers, younger workers' technology usage decisions were more strongly influenced by attitude toward using the technology. InWe thank Ttacy Ann Sykes of the University of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

44
617
17
21

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,174 publications
(751 citation statements)
references
References 56 publications
44
617
17
21
Order By: Relevance
“…Venkatesh et al (2003) found young users placed more importance on extrinsic reward (equivalent to PU). Similarly, Morris and Venkatesh (2002) found the same moderating effects of age. In addition, ''increased age has been shown to be associated with difficulty in processing complex stimuli and allocating attention to information on the job'' (Venkatesh et al, 2003, p. 450), implying that PEOU is a stronger determinant of BI for old users.…”
Section: Agesupporting
confidence: 54%
“…Venkatesh et al (2003) found young users placed more importance on extrinsic reward (equivalent to PU). Similarly, Morris and Venkatesh (2002) found the same moderating effects of age. In addition, ''increased age has been shown to be associated with difficulty in processing complex stimuli and allocating attention to information on the job'' (Venkatesh et al, 2003, p. 450), implying that PEOU is a stronger determinant of BI for old users.…”
Section: Agesupporting
confidence: 54%
“…It could be that collectively, new hires had developed technological skills regardless of age. Gender, however, was also not significant which is at odds with Morris and Venkatesh's (2000) and Cao et al's (2012) finding that gender has a significant influence on this relationship. Finally, with an increasing amount of Nigerian Millennials using social media during their university studies (Faese et al 2016), it was unclear why it is not being used more so at work.…”
Section: Discussionmentioning
confidence: 59%
“…This was contrary to many other studies which found being a female would influence use (Venkatesh et al 2016 (Venkatesh et al 2003;Venkatesh et al 2012). Morris and Venkatesh (2000) found that an age difference exists when it comes to technological adoption. Posner (1996) attributes a decline in cognitive capabilities that follows the aging process and corresponds to Prensky's (2001) theory of digital natives and digital immigrants, which suggests that people born in the 80's are most comfortable in using technology.…”
Section: Unified Theory Of Acceptance and Use Of Technologymentioning
confidence: 99%
“…Younger people are more receptive in adapting changes in the way they learn compared with older people (Bosma et al, 2003). Technology assimilation among older people is slower compared to younger people (Morris & Venkatesh, 2000). A study in Canada on teaching Mathematics using computer found that adult learners' academic performance was better when computers and teachers were used simultaneously.…”
Section: Agementioning
confidence: 99%